Glyoxylic Acid: A Carboxyl Group‐Assisted Metal‐Free Decarboxylative Reaction Toward Propargylamines. Issue 17 (5th May 2021) - Huang, Liliang; Xie, Yujuan; Ge, Panyuan; Huang, Junhai; Feng, Huangdi
Abstract: Readily available propargylamines are not only fundamental building blocks in organic synthesis, but also possess many prominent biological activities. A highly efficient, concise and environmentally benign decarboxylative reaction of glyoxylic acid monohydrate with secondary amines and alkynes has been elaborated, and a variety of propargylamines are delivered in moderate to good yields under metal‐free conditions. A mechanism involving a carboxyl group that assists the reactivity of alkynes, which makes the procedure of Michael addition proceeded smoothly, has been proposed. Abstract : A versatile metal‐free decarboxylative reaction of glyoxylic acid monohydrate with secondary amines and alkynes to produce propargylamines has been developed. In this reaction, the carboxyl group of glyoxylic acid can enhance the activation of the alkynes to react with iminium ion intermediate without any catalysts, thus increasing the sustainability of the process.